Using Information Technology to Enhance Customer Service - Veenapani, A. (Indian Journal of Marketing, 2006)
When an organization is selling its services or products to another organization or an individual, in many cases, a competitive advantage is gained by providing superb customer service. Information technology provides an advantage to the firms as it enhances the speed of operation and customer responsiveness with reduced cost and workplace flexibility. Information Technology improves service levels, by giving access to information, and has an increased geographic and demographic market reach. Technology is getting integrated, providing wider applicability and ease of use. With rapid growth in Information and communication technology, firms failing to utilize or adopt these technologies will be left far behind. Though the initial investments are high on the long run, the profits will offset the costs.Appropriate technology should be used by firms which best suits their business needs, in turn enhancing customer service, thereby creating a niche for themselves. Right from front end operations to back end operations, the entire supply chain can benefit from the use of Information technology.